Collage Lisnave, or the quest for architectural unity - Billi, Rebecca (2022)
According to Colin Rowe and Fred Koetter, as stated in their notorious book Collage City, the main difference between traditional and modern cities can be broken down to the concept that the matrix of the city itself has been transformed from continuous solid cut by voids, to a continuous void punctuated by buildings. The abandoned site of Lisnave stands as a symbol and embodiment of architectural disconnection and disunity, presenting itself as the forsaken remains of a disjoined urban complex, the roots of which can be found in the “modern planning” of the area itself, even though a proper urban masterplan of the site was never drafted if not for the construction plan of the industrial complex itself. At the same time, the industrialization that characterized its 20th Century history didn’t leave space for leisure nor did the unregulated urban growth implement what would be considered traditional forms of public or social space. A loss that can’t be overlooked, as the settlement itself owes its roots to this search for peace in nature, to the point that before being an industrialized suburbia, it was actually the arcadia to Lisbon’s chaotic city-ness. It now comes to architecture to intervene in a way that can overcome the disconnection that defines the urban character of Lisnave, to be able to present the area as a whole, to harmoniously bring these elements together through a system – one not limited by the constraints of a fixed program – an “open architecture” able to recreate the unity that was lost with the abandonment of the shipyard and reintroduce in the site spaces intended only to be enjoyed.